Source material for breeding winter bread wheat for grain quality in the north of the Middle Volga Region - I. D. Fadeeva; I. Yu. Ignatieva; A. G. Khakimova; O. P. Mitrofanova (Труды по прикладной ботанике, генетике и селекции)
Background. Development of cultivars with high stable yields and high grain quality is the main trend in wheat breeding. The aim of this study was to characterize a set of winter bread wheat accessions from the VIR collection and the working collection of Kazan Scientific Center in terms of their yield, protein content in grain (P, %), and swelling of flour in acetic acid (S, ml), and select the best accessions for the combination of these characters for use in a crossbreeding program.Materials and methods. Twenty-three winter bread wheat accessions were studied for the abovementioned characters in the north of the Middle Volga Region using conventional techniques. The study lasted three years (2016–2019).Results and conclusion. The yield of the accessions varied across the years of studies; however, none of them surpassed the reference cv. ‘Kazanskaya 560’. The values of protein content in grain were medium or high. The following accessions had high and stable levels of protein content in grain (15.1–16.1%): ‘TAW 42971/80’ (k-58363, Germany); ‘Lutescens 471 N8’ (Kazakhstan); ‘Rita’ (k-58057), ‘Scotty’ (k-59322) and ‘Nelson’ (all from the U.S.); ‘Moskovskaya 39’ (k-65160, Russia); ‘Bilotserkivchanka’ (k-64330) and ‘Barkan’ (k-64495) (both from Ukraine). Flour swelling power in acetic acid did not fall below 50 ml, attesting to the formation of high-quality grain. This was also confirmed by the protein quality index determined by the S : P ratio, which ranged from 3.6 to 4.7. Sources with high-quality protein were selected from the tested accessions for use in breeding: ‘CDC Clair’ (k-64168, Canada), ‘Lutescens 471 Н8’ (Kazakhstan), ‘Moskovskaya 39’ (Russia), ‘Barkan’ (Ukraine), and ‘Favorytka’ (k-64337, Ukraine).